(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
In the era of rapid globalization, the need for smooth understanding in communication, especially among people from different cultural background has become increasingly prevalent. The proliferation of technology has prompted numerous scholars to suggest that artificial intelligence (AI) may serve as a means to overcome this obstacle and promote intercultural dialogue. The present study investigates the prospective utilization of artificial intelligence (AI) in enhancing cross-cultural communication by means of translation. It also provides an overview of the contemporary advancements in artificial intelligence (AI) translation; including its benefits and drawbacks in promoting intercultural dialogue and underscores certain obstacles that require resolution to maximize its efficacy. The study involved the participation of 110 individuals, comprising of both language experts and professional translators. Furthermore, it utilized a questionnaire as the primary data collection tool, and subsequently employed descriptive-statistic method; wherein tables and graphs were used to analyze the data based on the two identified research questions. Many significant findings were made from the data which were presented and analyzed. The research findings suggest that AI-based translation technology holds considerable promise in enabling cross-cultural communication, as per the perspectives shared by language experts and professional translators who were involved in the study. Nevertheless, the study participants also identified the limitations of the use of AI translation tool in tackling some challenges in cross-cultural communication. Notwithstanding the efficacy of the aforementioned tool, the study recommends that further exploration and development in the area of AI-assisted translation to address its limitations and fully realize its potential benefits in the field of cross-cultural communication.